Determination of the lethal dose 50% (LD50) of cadmium chloride and the histopathological changes in male mice liver and kidneys - Talib Hussen Ali (College of Education for Pure Sciences, 2012)
ABSTRACT The lethal dose 50 (LD50) test involves the administration of cadmium in the form of CdCl2 to group of animals at an increasing dose in order to determine the dose that kills 50 percent of the test mice within a set of time frame (24 and 48h). The cadmium contents of liver and kidneys from dosed and control animals were determined by atomic absorption spectroscopy moreover, levels of alkaline phosphatase (ALP), in the target tissue were measured.. Male mice were dosed by 0.15ml cadmium (equivalent to the LD50 5.98 mg/kg body weight) in the form of CdCl2 via intraperitoneal injection for short-term treatment once per 24, 48 and 72h and, for long-term treatment once per week for 1, 4and 8 weeks then, sacrificed. The results showed that the effect of short-term and long-term Cd-administration on hepatic and renal Cd accumulation in the Swiss mice was found to be time dependent fashion. Atomic absorption examination showed that the Cd-content in both liver and kidneys increased significantly time dependent by 98-145% in liver and 100-300% in kidney at short-term treatment whereas for long-term treatment this increasing were 143-173% in liver and 200-370% in kidney respectively. This study also presents the histopathological effects in mice liver and kidney. Long-term Cd exposure produced damage to the entire kidney, including tubular degeneration, tubular cell apoptosis, interstitial inflammation and glomerular swelling and also resulted in liver injury including non-specific chronic inflammation and apoptosis, while it was less pronounced in short-term exposure.. Results of the biochemical profile indicated marked hepatic and renal toxic effect of cadmium reflected by the dramatic change in alkaline phosphatase (ALP) activity level, in the liver and kidney tissue. a significant increase (from100 to130%) in hepatic ALP activity, while the renal ALP activity level decreased by (from 95% to 65 %) as compared with those levels of the control in all relative periods of exposure.